Perbandingan Hasil Belajar Siswa dengan Model Projec Based Learning dan Problem Based Learning Berbantuan Media Chemsketch pada Materi Ikatan Kimia - Juniaty Berutu (Jurnal Pendidikan Indonesia, 2022)
The purpose of this study is to uncover, compare and record students' achievements and improvements in the application of two teaching techniques. The study conducted in two distinct MIPA tenth grade classes at SMAN 1 Tanjung Morawa. Project Based Learning model was used in MIPA 2, while Problem Based Learning model was used in MIPA 3. Both classes receive a pretest and a posttest, containing the same set of questions. Wilcoxon and N-Gain tests were used to assess the increase in student achievement in each class, and the independent sample t- test was used to compare the learning outcomes of the two models. The results showed an improvement in student achievement with positive scores in each class with a high category, meaning that the posttest value was greater than the pretest value. MIPA 2 has an N-Gain of 0.79, whereas MIPA 3 has an N-Gain of 0.72. However, the learning outcomes in the two classrooms varied significantly. Whereas the Independent Sample T-Test results show that the average posttest value for MIPA 2 class is lower than the average posttest value for MIPA 3 class, the value of Sig. (2-Tailed) is 0.001, which is less than the significant level of 0.05.